Sorption-based Energy Storage Systems: A Review - Thu, Kyaw; Nasruddin, Nasruddin; Mitra, Sourav; Saha, Bidyut Baran (Makara Journal of Technology, 2019)
Mismatched timing between the supply and demand of energy calls for reliable storage systems. Energy storage systems have become further significant with the widespread implementation of renewable energy. These systems can mitigate problems that are often associated with renewable energy sources such as supply unreliability while meeting the de-mand during peak hours. Energy can be stored in various forms, yet storage systems can be generally grouped based on their output forms, namely (i) electricity and (ii) heat or thermal energy. Electrical energy is the most convenient and effective form since it can power almost all modern devices. However, the electricity itself is vastly produced by ther-modynamic cycles at a particular thermal efficiency using thermal energy from fossil fuels. Meanwhile, thermal energy for the HVAC&R and the production of hot water remains the largest portion of the building energy sector. Thermal energy can be stored in the form of sensible, latent, and thermochemical energy. This review focuses on thermochemi-cal sorption-based energy storage systems. These systems exploit endothermic and exothermic sorption processes for charging and discharging of the thermal energy. Sorption-based storage systems exhibit huge potential due to a high energy density and their ability to store the energy at room temperature. We discuss the current state-of-the-art develop-ments, key challenges, and future prospects of sorption-based energy systems.